Generation of αGFP-nanobodies suitable for super-resolution imaging of nuclear proteins - Bachmann, Niklas (Student Undergraduate Research E-journal!, 2018)
The emergence of single molecule localization microscopy (SMLM) techniques made the imaging of cells at resolutions far beyond the diffraction barrier possible. However, the usual approach of tagging a protein of interest (PoI) with a primary antibody, and tagging this one with a fluorophore-carrying secondary antibody, introduces a significant displacement of the signal from the PoI. Here, the generation and application of an αGFP-nanobody is described which, through its reduced size and direct fluorophore labeling, leads to a much higher co-localization of signal and PoI and qualifies for dSTORM imaging of nuclear proteins.